2009
DOI: 10.2215/cjn.0200608
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Related Proteins

Abstract: Background: Because of the risk of performing renal biopsies in children with co-morbid conditions, we carried out this study to identify candidate protein biomarkers in the urine of HIV-infected children with renal disease.Design, setting, participants & measurements: Urine samples from HIV-infected children with biopsy proven HIVnephropathy (HIVAN; n ‫؍‬ 4), HIV-associated Hemolytic Uremic Syndrome (HIV-HUS; n ‫؍‬ 2), or no renal disease (n ‫؍‬ 3) were analyzed by two-dimensional electrophoresis (2-DE) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Furthermore, the upregulation of heme-oxygenase 1 suggests that iron trafficking and homeostasis plays a key role in renal IRI (23). The role of labile iron in potentiating renal injury may not be unique to IRI, as several iron-binding proteins have been detected in the urinary samples of children with human immunodeficiency virus nephropathy and urinary hepcidin-25 appears to be associated with renal relapse in lupus nephritis (24,25). This raises the possibility of a common renal injury pathway involving iron and iron-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the upregulation of heme-oxygenase 1 suggests that iron trafficking and homeostasis plays a key role in renal IRI (23). The role of labile iron in potentiating renal injury may not be unique to IRI, as several iron-binding proteins have been detected in the urinary samples of children with human immunodeficiency virus nephropathy and urinary hepcidin-25 appears to be associated with renal relapse in lupus nephritis (24,25). This raises the possibility of a common renal injury pathway involving iron and iron-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrosis and a quick decline in kidney function characterize HIV-associated nephropathy and HIVassociated uremic syndrome. Urinary NGAL levels, in two independent studies, were found to be significantly higher in these HIV-associated renal diseases than in HIV-positive and HIV-negative patients with other forms of chronic kidney disorders [24,25]. IgA nephropathy (IgAN) is the most common form of glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was successfully used for identification of potential biomarkers of different renal diseases. High urinary levels of β2-microglobulin, retinol-binding protein, transferrin, hemopexin, haptoglobin, lactoferrin, and neutrophil gelatinase-associated lipocalin (NGAL) were identified as candidate biomarkers for HIV-associated nephropathy [40]. Retinol-binding protein was also identified as a candidate biomarker for acute tubular necrosis [41].…”
Section: 1 Two-dimension Gel Electrophoresis (2de)mentioning
confidence: 99%